The Influence Of The Black Campaign Of The Presidential Candidate Pair's Successful Team On Beginner Voters at Fisip Upn Veteran Jakarta in The 2024 Election - Puspitaningrum, Dorothea; Ridwan (International Journal of Science and Society, 2024)
This research aims to analyze the influence of black campaigns conducted by the successful team of presidential candidate pairs on the behavior of novice voters at the Faculty of Social and Political Sciences (FISIP) UPN Veteran Jakarta in the 2024 Election. The research method used is a quantitative descriptive survey, utilizing a questionnaire distributed to FISIP UPN Veteran Jakarta students who are first-time voters. Data analysis techniques include descriptive tests and simple linear regression tests to determine the relationship between black campaigns and the behavior of first-time voters. The results showed that black campaigns significantly influenced the perceptions and decisions of first-time voters, as evidenced by a simple linear regression test with a regression coefficient of 0.564. This research supports the theory that negative information spread through campaigns can influence opinions and voting behavior, especially among first-time voters. It indicates that an increase in the intensity of black campaigns correlates with an increase in the responsiveness of first-time voters to negative information. Therefore, this research contributes significantly to understanding the dynamics of black campaign influence on first-time voters and emphasizes the importance of political literacy and critical awareness among voters to mitigate the negative impacts of black campaigns.